Impact of Intravenous Acetaminophen on Perioperative Opioid Utilization and Outcomes in Open Colectomies: A Claims Database Analysis. (July 2018) - Wasserman, Isaac; Poeran, Jashvant; Zubizarreta, Nicole; Babby, Jason; Serban, Stelian; Goldberg, Andrew T.; Greenstein, Alexander J.; Memtsoudis, Stavros G.; Mazumdar, Madhu; Leibowitz, Andrew B.
Abstract : Background: The value of intravenous acetaminophen in postoperative pain management remains debated. The authors tested the hypothesis that intravenous acetaminophen use, in isolation and in comparison to oral, would be associated with decreased opioid utilization (clinically significant reduction defined as 25%) and opioid-related adverse effects in open colectomy patients. Methods: Using national claims data from open colectomy patients (Premier Healthcare Database, Premier Healthcare Solutions, Inc., USA; 2011 to 2016; n = 181, 640; 602 hospitals), we separately categorized oral and intravenous acetaminophen use: 1 (1, 000 mg) or more than 1 dose on the day of surgery, postoperative day 1, or later. Multilevel models measured associations between intravenous or oral acetaminophen and (1) opioid utilization and (2) opioid-related adverse effects. Percent change and multiplicity-adjusted 99.5% CI are reported. Results: Overall, 25.1% of patients received intravenous acetaminophen, of whom 48.0% (n = 21, 878) received 1 dose on the day of surgery. In adjusted analyses, particularly more than 1 dose of intravenous acetaminophen ( versus nonuse) on postoperative day 1 was associated with a −12.4% (99.5% CI, −15.2 to −9.4%) change in opioid utilization. In comparison, a stronger reduction was seen in those receiving more than 1 oral acetaminophen dose: −22.6% (99.5% CI, −26.2 to −18.9%). Unadjusted group medians were 550 and 490 oral morphine equivalents, respectively. Intravenous versus oral differences were less pronounced among those receiving more than 1 acetaminophen dose on the day of surgery: −8.0% (99.5% CI, −11.0 to −4.9%) median 499 oral morphine equivalents versus −8.7% (99.5% CI, −14.4 to −2.7%) median 445 oral morphine equivalents, respectively; all statistically significant, but none clinically significant. Comparable outcome patterns existed for opioid-related adverse effects. Conclusions: The demonstrated marginal effects do not support routine use of intravenous acetaminophen given alternative nonopioid analgesic options. Abstract : A minority of open colectomy patients receive intravenous acetaminophen, which is mostly used as a single-dose administration on the day of surgery. A variety of intravenous acetaminophen dosing regimens were not observed to decrease opioid utilization to a clinically significant threshold.Supplemental Digital Content is available in the text.